Gendered experiences of unemployment, suicide and self-harm: a population-level record linkage study. Issue 16 (20th December 2022) - Cunningham, R.; Milner, A.; Gibb, S.; Rijnberg, V.; Disney, G.; Kavanagh, A. M.
Abstract: Background: Unemployment and being not in the labour force (NILF) are risk factors for suicide, but their association with self-harm is unclear, and there is continuing debate about the role of confounding by prior mental health conditions. We examine associations between employment status and self-harm and suicide in a prospective cohort, taking into account prior mental-health-related factors. Methods: We used linked data from the New Zealand Integrated Data Infrastructure. The outcomes were chosen to be hospital presentation for self-harm and death by suicide. The exposure was employment status, defined as employed, unemployed, or NILF, measured at the 2013 Census. Confounders included demographic factors and mental health history (use of antidepressant medication, use of mental health services, and prior self-harm). Logistic regression was used to model effects. Analyses were stratified by gender. Results: For males, unemployment was associated with an increased risk of suicide [odds ratio (OR): 1.48, 95% confidence interval (CI): 1.20–1.84] and self-harm (OR: 1.55, 95% CI: 1.45–1.68) after full adjustment for confounders. NILF was associated with an increased risk of self-harm (OR: 1.43, 95% CI: 1.32–1.55), but less of an association was seen with suicide (OR: 1.19, 95% CI: 0.94–1.49). For females, unemployment was associated with an increased risk of suicide (OR: 1.30, 95% CI: 0.93–1.80) and of self-harm (OR: 1.52, 95% CI: 1.43–1.62), and NILF was associated with a similar increase in risk for suicide (OR: 1.31, 95% CI: 0.98–1.75) and self-harm (OR: 1.32, 95% CI: 1.26–1.40). Discussion: Exclusion from employment is associated with a considerably heightened risk of suicide and self-harm for both men and women, even among those without prior mental health problems.